Avaliação do desempenho organizacional através da implantação da manutenção produtiva total - Bartz, Teonas (2011)
This study was conducted in a metallurgical company, a manufacturer of products with a production process with high precision equipment requiring effective maintenance to maintain the quality of the production process. The aim was the implementation of a maintenance management model based on Total Productive Maintenance - TPM in a production line of the company. To reach the proposed objective, we conducted an applied research, quantitative technique with the use of case study. Has been proposed the model for conducting the activities, emphasizing the training activities of the teams involved in the implementation, collection and analysis of indicators of industrial performance a year before the implementation of TPM. The development followed the timetable of activities and after application of the model of maintenance management, the results of these performance indicators were collected again. We observed that after the implementation of TPM, the indicators of industrial performance improvement and discussed incorporated positive trends for the following periods. Thus, it is concluded that the TPM assists in improving industrial performance and competitiveness of the production line studied.